Penyelesaian Sengketa Investasi Asing Melalui Mekanisme Arbitrase Internasional (Studi Kasus: Rafat Ali Rizvi Melawan Republik Indonesia) - Riezdiani Restu Widyoningrum (Student Research Journal, 2023)
One of the goals of the state is to create fair and prosperous society by carrying out development in various fields including the fields of economy, education and infrastructure. The country's development certainly requires large amounts of funds, but not all countries have these funds. The lack of funds which needed by the state is an entry point for investors to invest their capital, which is through foreign investment. Besides the investment, foreign investment also brings expertise, technology transfer, and can increase the productivity of the host country. However, the implementation of foreign investment do not always go well, investment problems will arise and in the end it can become foreign investment dispute. Investment dispute settlement is an important part of foreign investment in Indonesia and that is the form of protection for foreign investors. Investment disputes settlement in Indonesia begins with deliberation and consensus. If the deliberation and consensus not achieved, then the parties can take investment dispute settlement through international arbitration. The most common international investment dispute settlement mechanism is Investor-State Dispute Settlement (ISDS). Beside that, there is State-State Dispute Settlement (SSDS) mechanism. Submission of international investment disputes can be submitted to international arbitration forums, through International Centre for Investment Dispute (ICSID). One of the cases of foreign investment disputes that involved Indonesia is between Rafat Ali Rizvi and Republic of Indonesia.